Difference in the Gut Microbiome between Ovariectomy-Induced Obesity and Diet-Induced Obesity - Choi, Sungmi; Hwang, Yu-Jin; Shin, Min-Jeong; Yi, Hana (Journal of microbiology and biotechnology, 2017)
During menopausal transition, the imbalance of estrogen causes body weight gain. Although gut microbiome dysbiosis has been reported in postmenopausal obesity, it is not clear whether there is any difference in the microbiome profile between dietary-induced obesity and postmenopausal obesity. Therefore, in this study, we analyzed intestinal samples from ovariectomized mice and compared them with those of mice with high-fat diet-induced obesity. To further evaluate the presence of menopause-specific bacteria-gene interactions, we also analyzed the liver transcriptome. Investigation of the 16S rRNA V3-V4 region amplicon sequence profile revealed that menopausal obesity and dietary obesity resulted in similar gut microbiome structures. However, was exclusively observed in the ovariectomized mice, which indicated that menopausal obesity resulted in a different intestinal microbiome than dietary obesity. Additionally, several bacterial taxa ( species, , and species) were found when the ovariectomized mice were treated with a high-fat diet. A significant correlation between the above-mentioned menopause-specific bacteria and the genes for female hormone metabolism was also observed, suggesting the possibility of bacteria-gene interactions in menopausal obesity. Our findings revealed the characteristics of the intestinal microbiome in menopausal obesity in the mouse model, which is very similar to the dietary obesity microbiome but having its own diagnostic bacteria.